Percutaneous epidural drainage through a burr hole - Falsarella, Priscila M (Indian J Radiol Imaging, 2016)
Intracranial extradural collection may cause an increase in intracranial pressure, requiring rapid emergency treatment to reduce morbidity and mortality. We described an alternative CT-guided percutaneous access for extradural collection drainage. We report a case of a patient with previous craniectomy for meningioma ressection who presented to the Emergency Department with symptoms of intracranial hypertension. Brains CT showed a extradural collection with subfalcine herniation. After multidisciplinary discussion a CT-guided percutaneous drainage through previous burr hole was performed. The patient was discharged after 36 hours of admission, without further symptoms. We describe a safe and effective alternative percutaneous access for extradural collection drainage in patients with previous burr hole.